Dukungan Sosial Konselor Adiktif dan Keluarga dalam Program Rehabilitasi Pecandu Narkoba - Iwan Joko Prasetyo; Didik Sugeng Widiarto; Nur Annafi FSM; Yenny, Yenny; Widya Desary Setia Wardhani (Yayasan Literasi Sains Indonesia, 2024)
The problem of drug abuse is truly disturbing for the government and society throughout Indonesia. Every year the prevalence rate of drug abuse always increases. Efforts are needed to eradicate the distribution and use of drugs in society. One of the efforts is a social and medical rehabilitation program for drug addicts. The success of the rehabilitation program must be supported by professional social support sources, namely addiction counselors and non-professional sources, namely the family. Various forms of social support provided by addiction counselors and families really help restore the physical and mental condition of drug addicts to become healthy and productive individuals again. The aim of this research is to find out and explore the forms of social support provided by addiction counselors and families in the rehabilitation program for drug addicts at the Doulos Batu Recovery Center. The research method used is a qualitative method with a case study approach. Meanwhile, the research informants were 2 addiction counselors and 2 clients/residents. The research results show that social support in the form of emotional support, tangible or instrumental support, informational support, and companionship support can restore clients' social capabilities and social responsibility so that they can return to being healthy and productive humans.